Geographical Accuracy of Place-Based Collegiate Athletic Conference Names in the United States - Michael D. Sublett (Names, 2020)
College athletic competition constitutes a significant aspect of life in the United States. Virtually, every institution of higher learning fields intercollegiate teams in a multitude of sporting activities. Most colleges and universities join an organization, a conference of similar institutions, to enhance competition. Some also join single-sport conferences in order to participate in sports that their principal conferences do not accommodate. All conferences have names, often place-based names. Many place-based names convey their conference locations well; others fail in this regard. This essay examines the names of all 184 baccalaureate-level conferences in the United States, excludes those conference names that do not have a place basis, and divides the remaining conferences into two categories: those whose names are place appropriate and those that are not.